1994
DOI: 10.1002/mcs.1220060604
|View full text |Cite
|
Sign up to set email alerts
|

Hydrofluorocarbon and perfluorocarbon mobile phases for capillary supercritical fluid chromatography

Abstract: Abstract. The eluotropic strength of several hydrofluorocarbon and perfluorocarbon supercritical fluids is examined using capillary supercritical fluid chromatography. The results obtained are compared with carbon dioxide, fluoroform, and carbon dioxide modified with 5 % methanol. Various naphthalene derivatives are used to determine differences in functional group selectivity between these fluids. Specific hydrogen bonding interactions are observed between hydrogen bond donating hydrofluorocarbon fluids and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Earlier studies have indicated that HFC-134a (1,1,1,2-tetrafluoroethane) is extremely high in eluotropic strength compared to carbon dioxide or methanol-modified carbon dioxide mobile phases for the elution of naphthalene derivatives with a wide range of polarity. 4,5 These results have been obtained on both non-polar, open-tubular capillary columns and highly polar, bare silica packed columns. A mobile phase consisting primarily of HFC-134a should, therefore, be suitable for elution of polar pharmaceutical compounds.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Earlier studies have indicated that HFC-134a (1,1,1,2-tetrafluoroethane) is extremely high in eluotropic strength compared to carbon dioxide or methanol-modified carbon dioxide mobile phases for the elution of naphthalene derivatives with a wide range of polarity. 4,5 These results have been obtained on both non-polar, open-tubular capillary columns and highly polar, bare silica packed columns. A mobile phase consisting primarily of HFC-134a should, therefore, be suitable for elution of polar pharmaceutical compounds.…”
mentioning
confidence: 61%
“…13 The retention data given in Table 1 are quite contrary to the observations made regarding relative eluotropic strength of carbon dioxide and HFC-134a. 4,5 Earlier studies showed pure HFC-134a to be far higher in eluotropic strength than either carbon dioxide or methanol-modified carbon dioxide on a variety of stationary phases. The primary difference here is that the HFC-134a mobile phases themselves contain a significant amount of modifier.…”
Section: Retentionmentioning
confidence: 98%
“…Several perfluorocarbon solvents have been used successfully in fluorous separations 19,41-45. In comparison to conventional organic solvents, typical perfluoroalkanes are considered to be both fluorophilic and extraordinarily non-polar solvents, whereas perfluorinated ethers are classified as fluorophilic but more polar solvents 12,13.…”
Section: Resultsmentioning
confidence: 99%
“…Recently researchers employed R134a directly or employed it as a modifier of supercritical fluid carbon dioxide (SFCO 2 ) in SFC. [9][10][11][12][13][14] It was demonstrated that R134a had different selectivities and solvation power than carbon dioxide and methanol-modified carbon dioxide in SFC. Its calculated solubility parameters 15 at 100°C and 300 bar, and 200°C and 400 bar are 6.32 and 5.12, respectively, compared to 4.95 and 3.59 for CO 2 , indicating a higher solvating power.…”
Section: Introductionmentioning
confidence: 99%